2022
DOI: 10.3390/f13050708
|View full text |Cite
|
Sign up to set email alerts
|

Water Uptake Pattern by Coniferous Forests in Two Habitats Linked to Precipitation Changes in Subtropical Monsoon Climate Region, China

Abstract: Variations in precipitation patterns under climate changes influence water availability, which has important implications for plants’ water use and the sustainability of vegetation. However, the water uptake patterns of the main forest species under different temporal spatial conditions of water availability remain poorly understood, especially in areas of high temporal spatial heterogeneity, such as the subtropical monsoon climate region of China. We investigated the water uptake patterns and physiological fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 69 publications
0
0
0
Order By: Relevance
“…Photosynthesis and transpiration in plants are disproportionately driven by environmental factors, and the stomatal opening directly determines the magnitude of P n and E. Some studies have suggested that light is the driving source of photosynthesis and water transpiration in leaves [42] and that there is a relatively stable proportional relationship between the light used to drive photosynthesis and the light used to drive transpiration [43]. Other studies have found that temperature directly affects the saturated water vapour pressure deficit inside and outside the leaves [44], thus, affecting stomatal openness and the transpiration rate and ultimately affecting plant photosynthesis. In the current study, it was found that leaf P n and E showed diurnal and seasonal changes with changes in light and temperature during the growing season.…”
Section: Effects Of Environmental Factors On Pn − E Couplingmentioning
confidence: 99%
“…Photosynthesis and transpiration in plants are disproportionately driven by environmental factors, and the stomatal opening directly determines the magnitude of P n and E. Some studies have suggested that light is the driving source of photosynthesis and water transpiration in leaves [42] and that there is a relatively stable proportional relationship between the light used to drive photosynthesis and the light used to drive transpiration [43]. Other studies have found that temperature directly affects the saturated water vapour pressure deficit inside and outside the leaves [44], thus, affecting stomatal openness and the transpiration rate and ultimately affecting plant photosynthesis. In the current study, it was found that leaf P n and E showed diurnal and seasonal changes with changes in light and temperature during the growing season.…”
Section: Effects Of Environmental Factors On Pn − E Couplingmentioning
confidence: 99%